Os estudantes do arquivo morto - Ferrão, Luciana Vigil (2010)
This research, linked to the Research Line School Practice and Public Policy, the PPGE / UFSM has research problem that arises in the context of a school of elementary education, secondary education, in which the researcher operates. This is associated with higher dropout rates and is stated as: which one (s) cause (s) of school dropout, high school, the State Institute of Education Vicente Dutra? The purpose of this research is to investigate and discuss possible causes of this avoidance, with students outside school as well as identify resizes to help address this problem. In terms of theoretical and methodological routing, this can be construed as qualitative research, the case study, using instruments like a questionnaire and a semi-structured interview. The research subjects were students who escaped the school and who did not return. In analyzing the results, we opted to content analysis. Identified causes, research, to escape, were summarized in three categories: 1) comply with programs, 2) Interest: make sense to be in school and 3) curriculum naturalized. The theoretical sought to involve authors in the area on the environment of primary schools with regard to the constitution in this space and time, the influence of the curriculum in this constitution, as well as production has already started work on truancy and the support of authors who argue that under the approach exclusion rather than academic failure.